# What are the solutions to the equation 0=x squared- x-6

Factor to this equation out, the easiest way is to solve for the two x values that add up to -1 but when multiplied is equal to -6. It should look like this: (x +- ?)(x +- ?).

The factored out form is then (x - 3)(x +2), because -3 + 2 = -1 and when multiplied together gives -6.

x - 3 = 0

x = 3

x + 2 = 0

x = -2

The two solutions are therefore, x = 3 and x = -2.

## Related Questions

Solve F(x) for the given domain.F(x)= x2 + 3x-2
F(-1) =
Jutaານເພະາ
a. -4
b. -6
C. 2.​

A. -4

Step-by-step explanation:

F(-1) means we must plug the number "-1" in for each x.

F(x) = x^2 + 3x - 2

F(-1) = (-1)^2 + 3(-1) - 2

= 1 - 3 - 2

= -4

Jacob made a banner for a sporting event in the shape of a parallelogram. The area of the banner is 127 1/2 square centimeters. The height of the banner is 4 1/4 centimeters. What is the base of the banner?

Step-by-step explanation: its 30 because you divide 127 1/2 or 127.5 by 4.25 or 4 1/4.

You want to rent an unfurnishedone-bedroomapartment for next semester. The mean monthlyrent for a random
sample of 10 apartments advertised in the localnewspaper is $580. Assume that the standard deviation is$90. Find a 95% confidence
interval for the mean monthly rentfor unfurnished one bedroom
apartments available for rent in thiscommunity.

Step-by-step explanation:

Confidence interval for population mean is given by :-

, where = Sample mean

z* =  critical z-value.

= Population standard deviation.

n= Sample size.

Let x be the denotes the monthly rent for unfurnished one bedroom  apartments available for rent in this community.

As per given , we have

n= 10

Critical value for 95% confidence : z* = 1.96

So the 95% confidence  interval becomes,

Hence, a 95% confidence  interval for the mean monthly rent for unfurnished one bedroom  apartments available for rent in this community=

Suppose that B1 and B2 are mutually exclusive and complementary events, such that P(B1 ) = .6 and P(B2) = .4. Consider another event A such that P(A | B1) = .2 and P(A | B2) = .5. Find P(A).

So, we get that is P(A)=0.32.

Step-by-step explanation:

We know that:

We have the formula for probability:

So, we calculate:

We calculate:

So, we get that is P(A)=0.32.

To find P(A), use the law of total probability given that B1 and B2 are mutually exclusive and complementary events. Substituting the provided values, P(A) = 0.32.

### Explanation:

The question is asking us to calculate P(A), given the values for P(A | B1) and P(A | B2), and the knowledge that B1 and B2 are mutually exclusive and complementary events. In probability, if events B1 and B2 are mutually exclusive and complementary, this means that one and only one of them can occur, and their occurrence covers all possible outcomes. We can use the law of total probability to find the overall P(A). The law of total probability states that P(A) = P(A | B1) * P(B1) + P(A | B2) * P(B2). Plugging the provided values into this formula, we get P(A) = .2 * .6 + .5 * .4 = .12 + .2 = .32. Therefore, P(A) is .32.

brainly.com/question/22962752

#SPJ11

During the soccer season, Cathy made 27 of the 54 goals she attempted. Karla made 18 of the 45 goals she attempted. Patty made 34% of the goals she attempted. List the athletes in order of their goal-scoring percentage from least to greatest.

Patty, Karla, Cathy

Step-by-step explanation:

The scoring percentage of goals attempted can be computed by dividinggoals made by those attempted, then multiplying the result by 100%.

__

Cathy's rate is ...

27/54 × 100% = 50%

Karla's rate is ...

18/45 × 100% = 40%

Patty's rate is ...

given as 34%

__

By least to greatest scoring rate, the athletes are ...

Patty (34%), Karla (40%), Cathy (50%)

F(x)=5x2−3x−1 and g(x)=2x2−x+3f(x)+g(x)=
Question 18 options:

3x2−4x−4

3x2−2x−4

7x2+4x+3

7x2−4x+2

f(x) + g(x) = 7x² - 4x + 2

General Formulas and Concepts:

Algebra I

• Combining Like Terms

Step-by-step explanation:

Step 1: Define

f(x) = 5x² - 3x - 1

g(x) = 2x² - x + 3

Step 2: Find f(x) + g(x)

1. Substitute:                                f(x) + g(x) = 5x² - 3x - 1 + 2x² - x + 3
2. Combine like terms (x²):          f(x) + g(x) = 7x² - 3x - 1 - x + 3
3. Combine like terms (x):            f(x) + g(x) = 7x² - 4x - 1 + 3
4. Combine like terms (Z):           f(x) + g(x) = 7x² - 4x + 2